Prevalence of suicidal ideation, plan, attempts and its associated factors in selected rural and urban areas of Puducherry, India. (17th July 2020) - Singh, Aakanksha; Saya, Ganesh Kumar; Menon, Vikas; Olickal, Jeby Jose; Ulaganeethi, Revathi; Sunny, Roshina; Subramanian, Sadhana; Kothari, Ashutosh; Chinnakali, Palanivel
Abstract: Background: The Union Territory of Puducherry has a high rate of suicide in India. This study aims to find the prevalence of suicidal ideation, plan and suicide attempts and the risk factors of suicidal behaviours. Methods: This community-based cross-sectional study was conducted among adults aged 18 years and above in rural and urban areas of Puducherry, India. Columbia Suicide Severity Rating Scale questionnaire was used. Prevalence ratio was estimated to assess the factors associated. Results: The 12-month and lifetime prevalence of suicidal ideation was reported to be 12.5% (95% CI: 10.4–15.0%) and 20% (95% CI: 17.4–22.9%), respectively. About 0.7% (95% CI: 0.3–1.5%) and 2.1% (95% CI: 1.2–3.3%) of the participants had suicide plan in past 12 months and ever in their lifetime, respectively. Around 1% (95% CI: 0.5–2.0%) and 5.7% (95% CI: 4.3–7.6%) of the participants had attempted suicide in past 12 months and ever in their lifetime, respectively. Family issues, physical abuse, unemployment and place of residence were significantly associated with suicidal ideation in multivariable analysis. Conclusion: Prevalence of suicidal ideation and suicide attempt were very high in the study area. Unemployment, physical abuse and family issues were significantly associated with suicidal behaviour.